Propositional clothing and belief - Sinclair, Neil (Wiley, 2007)
Moral discourse is propositionally clothed, that is, it exhibits those features – such as the ability of its sentences to intelligibly embed in conditionals and other unasserted contexts – that have been taken by some philosophers to be constitutive of discourses that express propositions. If there is nothing more to a mental state being a belief than it being characteristically expressed by sentences that are propositionally clothed then the version of expressivism which accepts that moral discourse is propositionally clothed (‘quasi-realism’) is self-refuting. Fortunately for quasi-realists, this view of belief, which I label ‘minimalism’, is false. I present three arguments against it and dismiss two possible defences (the first drawn from the work of Wright, the second given by Harcourt). The conclusion is that the issue between expressivists and their opponents cannot be settled by the mere fact that moral discourse wears propositional clothing.